Spatial distribution of mangrove vegetation species, salinity, and mud thickness in mangrove forest in Pangarengan, Cirebon, Indonesia - RIS HADI PURWANTO; BUDI MULYANA; RYAN ADI SATRIA; EMAD HASSAN ELAWAD YASIN; ILHAM SATRIA RADITYA PUTRA; AGIK DWIKA PUTRA (Society for Indonesian Biodiversity, 2022)
Abstract. Purwanto RH, Mulyana B, Satria RA, Yasin EHE, Putra ISR, Putra AD. 2022. Spatial distribution of mangrove vegetation species, salinity, and mud thickness in mangrove forest in Pangarengan, Cirebon, Indonesia. Biodiversitas 23: 1384-1392. The mangrove rehabilitation programs in the northern coastline of West Java showed varying levels of success due to the lack of information on habitat suitability and species distribution. This research aimed to investigate the spatial distribution of mangrove vegetation species, salinity, and mud thickness in Pangarengan mangrove forest, Cirebon, Indonesia. Data on mangrove vegetation, salinity, and mud thickness were collected from 78 randomly distributed sample plots. Species composition was analyzed using important value index, and spatial distribution was examined using QGIS. Results revealed that Rhizophora mucronata was the most dominant and widely distributed species in all areas of Pangarengan mangrove forest with the important value index (IVI) for seedlings, saplings, poles, and trees were 178.69%, 219.71%, 242.21%, and 167.56%, respectively. Avicennia marina showed significant IVI in saplings (59.41%) and trees (105.21%). Other species had an IVI of less than 20% for each growth stage. Salinity ranged from 0-28 ppt and gradually decreased from the shoreline to settlement areas. Mud thickness ranged from 55 to 175 cm but with no regular pattern observed. In conclusion, the Pangarengan mangrove forest was dominated by R. mucronata. Our findings suggest that to enhance the likelihood of success in mangrove rehabilitation programs, R. mucronata might be a good choice, but to increase the species diversity other species might need to be planted by applying specific treatments, such as a vertical aquaponic system.